Heat-conducting color master batch as well as preparation method and application thereof
By using the thermal masterbatch composed of graphite emulsion, surface adsorbent and base resin in the plastic sealing material, the silicon dioxide particles are bridged to form a thermal channel, which significantly improves the thermal conductivity of the plastic sealing material, and solves the difficulty in improving the optimization of traditional fillers and interface structures. The problem of thermal conductivity improves the thermal conductivity and mechanical properties of the material.
Patent Information
- Application Number
- CN202411501145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
AI Technical Summary
The thermal conductivity of existing plastic sealing materials is insufficient, especially when subjected to high temperatures during packaging and reflow soldering, which affects product reliability, and traditional filler and interface structure optimization is difficult to significantly improve thermal conductivity.
The thermal conductivity masterbatch composed of graphite emulsion, surface adsorbent and base resin is used as the colorant, and the thermal conductivity of the plastic sealing material is significantly improved by bridging the graphite emulsion with silica particles.
Through the application of thermal masterbing, the thermal conductivity of plastic sealing materials is significantly improved, efficient thermal conductivity channels are formed, and the thermal conductivity and mechanical properties of the materials are enhanced, solving the problem that traditional fillers and interface structure optimization are difficult to improve thermal conductivity.
Smart Images

Figure CN119286198A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a thermal conductive masterbatch and a preparation method and application thereof. Background Art
[0002] Epoxy molding compound is mainly composed of epoxy resin, cross-linking curing agent, curing accelerator and additives. Due to its many outstanding characteristics, such as good thermal stability, insulation, adhesion, good mechanical properties, excellent molding process performance and low cost, it is widely used in the field of electronic component packaging, and has become one of the most important electronic chemical materials. In recent years, with the continuous development of advanced microelectronics technology, electronic packaging has become increasingly lightweight. Traditional powder packaging and solvent-containing liquid packaging have been gradually replaced by compression molding products due to their packaging defects and damage to the environment. Especially in modular circuits and integrated circuits, this packaging form is more widely used to achieve lightweight and miniaturization of products.
[0003] Due to the change of magnetic induction packaging from powder encapsulation and liquid impregnation to compression molding, the fillers are all metal alloys and high thermal conductivity materials. During the packaging and reflow soldering process, the plastic packaging material is subjected to high temperatures, which causes the plastic packaging material to expand and internal stress. This makes it easy for the plastic packaging material and the chip to be delaminated. In severe cases, the product may crack or even popcorn, which greatly affects the reliability of the product. At the same time, due to the limited size reduction of inductor devices, the current packaging products have poor thermal conductivity, low magnetic permeability, and poor inductance performance.
[0004] How to achieve high thermal conductivity is the focus of research and development of electronic packaging plastic materials. Most of the research reported in the literature achieves this by replacing various high thermal conductivity fillers or optimizing the filler and interface structure.
[0005] Chinese patent CN201910956506.2 discloses an epoxy molding compound for high thermal conductivity and high magnetic induction packaging, which is made of epoxy resin, curing agent, curing accelerator, inorganic filler, release agent, modifier and composite coupling agent. The patent improves the thermal conductivity of epoxy molding compound by combining magnetic thermal conductive filler with multiple organic materials such as polyaromatic epoxy resin, cyclopentadiene epoxy, flexible epoxy resin, polyaromatic curing agent, linear phenolic curing agent, etc.
[0006] Chinese patent CN201811290986.5 discloses a super heat-resistant and highly thermally conductive epoxy molding compound for semiconductor packaging, which contains the following components: 45-127.5 parts by weight of epoxy resin, 60-300 parts by weight of curing agent, 3.75-10.35 parts by weight of ion capture agent, 3.9-15 parts by weight of low stress modifier, 3-6.75 parts by weight of coupling agent, 0.9-9 parts by weight of promoter, 525-672.25 parts by weight of solid filler, 3-12 parts by weight of release agent, 2.25-5.25 parts by weight of flame retardant, and 1.5-2.25 parts by weight of colorant. The patent adds ester ring epoxy resin, heterocyclic epoxy resin, naphthalene ring epoxy resin, and multifunctional epoxy resin as resin matrix to the epoxy molding compound to improve the glass transition temperature of the material and increase the heat resistance of the material.
[0007] However, there has been no research and development report on improving the colorants used in plastic packaging materials. How to improve the thermal conductivity of plastic packaging materials through colorants is a major problem facing the plastic packaging material industry. Summary of the invention
[0008] The purpose of the present invention is to provide a thermal conductive masterbatch and its preparation method and application. By using the thermal conductive masterbatch prepared by the present invention as a colorant in a plastic packaging material, the thermal conductivity of the plastic packaging material can be significantly improved. The thermal conductive masterbatch of the present invention can bridge isolated silicon dioxide particles of different sizes to form an effective thermal conductive channel, thereby effectively improving the thermal conductivity.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] A thermal conductive masterbatch is composed of graphite emulsion, surface adsorbent and base resin, wherein the content of the graphite emulsion in the thermal conductive masterbatch is not less than 70wt%.
[0011] Further, the thermal conductive masterbatch comprises the following raw materials in terms of mass percentage:
[0012] Graphite emulsion 70% ~ 90%,
[0013] Surface adsorbent 1% ~ 3%,
[0014] Base resin 8% ~ 27%.
[0015] Furthermore, the preparation method of the graphite emulsion is as follows:
[0016] S1, mixing graphite powder, a solvent and a dispersant to obtain a graphite slurry;
[0017] S2. Purify the graphite slurry obtained in step S1 to obtain graphite emulsion.
[0018] Furthermore, in step S1, the graphite powder is ultrafine flaky microcrystalline graphite powder.
[0019] Furthermore, in step S1, the co-solvent is a ketone solvent or an alcohol solvent.
[0020] In the above further embodiment, the ketone solvent includes acetone, butanone, cyclohexanone, methyl isobutyl ketone and isophorone.
[0021] Furthermore, in the above, the alcohol solvent includes ethanol, n-propanol and isopropanol.
[0022] Furthermore, in step S1, the dispersant is selected from any one of sorbitol ester, monoglyceride, gelatin, and nano-silica gel.
[0023] Furthermore, in step S2, the purification method is selected from static separation or low-speed centrifugal separation.
[0024] Furthermore, in step S2, the graphite slurry obtained in step S1 is purified and dried to obtain graphite emulsion.
[0025] The drying temperature is 120-160°C, preferably 140°C;
[0026] The drying time is 2 to 4 hours, preferably 3 hours.
[0027] The graphite emulsion preparation specifically requires ultrafine flake powder dispersion and purification, which includes a cosolvent and a dispersant; in order to extract ultrafine particles and achieve dispersion, it is necessary to stand for 7 days and take the upper clear liquid; and according to higher thermal conductivity and insulation requirements, low-speed centrifugation (speed below 1000RPM) is required to separate coarse particles or granular particles.
[0028] Furthermore, the surface adsorbent includes a physical surface treatment component and / or a chemical surface treatment component.
[0029] Furthermore, when the surface adsorbent includes both a physical surface treatment component and a chemical surface treatment component, the ratio of the physical surface treatment component to the chemical surface treatment component in the surface adsorbent is 1:1.5-2.5.
[0030] In the above further embodiment, the physical surface treatment component is an organic liquid, and the physical surface treatment component is selected from any one or more of poly-alpha-olefins, polyolefins, polycyclic aromatic hydrocarbons or polycyclic aromatic ethers.
[0031] In the above, further, the chemical surface treatment component is a cross-linking agent, and the chemical surface treatment component includes any one or more of acrylate, polypyrrole, polyvinyl alcohol, KH550, KH560, KH570 and a chelating agent, and the chelating agent includes EDTA, BAPTA and carboxymethyl chitosan.
[0032] Furthermore, the base resin includes epoxy resin and / or phenolic curing agent.
[0033] As a preferred technical solution, the mass content of the epoxy resin and the phenolic curing agent in the base resin is calculated according to the epoxy equivalent of the epoxy resin and the hydroxyl equivalent ratio of the phenolic curing agent. In the above further, the epoxy resin includes o-cresol epoxy resin, bisphenol A type epoxy resin, biphenyl type epoxy resin, phenol aralkyl epoxy resin, dicyclopentadiene type epoxy resin, multifunctional epoxy resin and naphthalene ring structure epoxy resin.
[0034] In the above, the phenolic curing agent includes linear phenolic resin, para-tert-butyl phenolic resin, MAR phenolic resin, MAR phenolic resin (XYLOK), MAR phenolic resin (biphenyl type) and MFN multifunctional phenolic resin.
[0035] As a preferred technical solution, the base resin is obtained by physically mixing or blending epoxy resin and phenolic curing agent. Physical mixing means using part of epoxy resin and part of phenolic curing agent, which can prevent the base resin from premature cross-linking, but the uniformity may be slightly lower;
[0036] Physical blending refers to mixing epoxy resin and phenolic curing agent together, which has good uniformity, but premature cross-linking is inevitable. However, because the curing system reacts very slowly, no obvious cross-linking will occur within a limited time (the time is well controlled, generally within 45 minutes as mentioned above).
[0037] The present invention also provides a method for preparing a thermally conductive masterbatch, and the specific steps are as follows:
[0038] S1. Surface adsorption enhancement treatment: Graphite emulsion is modified by adding surface adsorbent;
[0039] S2. Masterbatch mixing process: The modified and refined graphite emulsion is mixed with the base resin at high temperature to remove the co-solvent and dispersant to obtain the thermal conductive masterbatch.
[0040] Furthermore, in step S2, the banburying temperature is 100-180° C., the banburying speed is 30-180 rpm, and the banburying time is 5-45 minutes.
[0041] Depending on the base resin, the mixing temperature, speed and time are adjusted to "solidify" the dispersion effect through the solid resin medium at room temperature.
[0042] In addition, the present invention also provides an application of a thermally conductive masterbatch, wherein the thermally conductive masterbatch is used as a colorant in a plastic packaging material.
[0043] Furthermore, the molding compound is composed of silicon powder, epoxy resin, phenolic curing agent, silicone oil, demoulding wax and thermal conductive masterbatch, and the mass content of the epoxy resin and phenolic curing agent is calculated according to the epoxy equivalent of the epoxy resin and the hydroxyl equivalent ratio of the phenolic curing agent.
[0044] Furthermore, when the epoxy resin is o-cresol epoxy resin and the phenolic curing agent is linear phenolic resin, the plastic encapsulation material includes the following raw materials in terms of mass percentage:
[0045]
[0046] As a preferred technical solution, the silicon micropowder is selected from silicon nitride micropowder or silicon dioxide micropowder;
[0047] The demoulding wax is selected from any one or more of carnauba wax, synthetic wax and mineral wax.
[0048] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0049] The colorant used in general plastic encapsulation materials is carbon powder or masterbatch. The essence of masterbatch is still carbon powder, and flake micro-powder graphite, which is also one of the allotropes of carbon, is an excellent thermal conductive material. If the flake micro-powder graphite can be evenly dispersed in the plastic encapsulation material, the thermal conductivity of the plastic encapsulation material can be further significantly improved without occupying additional filler content.
[0050] The thermal conductive filler provided by the present invention needs to be finely ground and dispersed to ensure that it can be evenly distributed in the polymer matrix. During the dispersion process, it is necessary to purify and remove impurities or unnecessary components in the filler to improve the purity and thermal conductivity of the overall material. In order to enhance the interface bonding between the thermal conductive filler and the polymer matrix, the filler surface is usually physically and chemically treated to help improve the affinity between the filler and the matrix, thereby improving the mechanical properties and thermal conductivity efficiency of the composite material. After the surface treatment, the filler and the carrier resin are mixed by a mixer. Mixing is a high shear process that can fully mix the various components at high temperature to form a uniform thermal conductive masterbatch.
[0051] The heat conduction mechanism of the present invention is that the graphite component of the heat-conducting colorant forms a heat conduction channel with a heterogeneous component that significantly exceeds its own conditions. The system used has a graphite equivalent particle size of <1 micron and a content of less than 0.5% Vol; while the basic silica filler has a D90 particle size of 12 microns and a content of more than 70% Vol. The potential number of connections and the surface area of the channels that can be formed are much higher than those of the graphite component, and the volume content of silica also exceeds that of "diamond" under the same thermal conductivity coefficient, providing favorable conditions for graphite particles to form heat conduction channels with the help of silica, that is, the heterogeneous heat conduction bridging effect of graphite particles; and from the analysis results of the heat conduction energy efficiency ratio, it can be inferred that the heterogeneous bridging has been fully manifested. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a SEM image of the plastic encapsulation material in Example 3 of the present invention, wherein the yellow arrows indicate carbon particles;
[0053] Figure 2 This is a SEM image of the plastic encapsulation material in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0054] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0055] In the following examples, the sources of the materials are as follows:
[0056] The ultrafine flaky microcrystalline graphite powder was purchased from Qingdao Huatai Nano-Grade Graphite Powder;
[0057] The polyolefin was purchased from Dow Chemical Company of the United States;
[0058] The polyvinyl alcohol was purchased from Changchun Chemical (Jiangsu) Co., Ltd., with the brand name BM-17;
[0059] The o-cresol epoxy resin is purchased from N-665 of DIC Corporation of Japan;
[0060] The silicon powder was purchased from QG75, Yunnan Nonmetallic Minerals Research Institute;
[0061] The linear phenolic resin was purchased from Nippon Kayaku, brand: NC3000;
[0062] The silicone oil was purchased from Dow Corning, brand: 8421;
[0063] The carnauba wax is purchased from carnauba wax;
[0064] The conventional colorant (carbon powder) was purchased from Degussa Carbon Black SB6.
[0065] In conjunction with the accompanying drawings, some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.
[0066] Example 1
[0067] This embodiment provides a thermal conductive masterbatch, which includes the following raw materials in percentage by mass:
[0068] Graphite emulsion 70%,
[0069] Surface adsorbent 3%,
[0070] Base resin 27%.
[0071] In this embodiment, the surface adsorbent includes 2% polyolefin and 1% polyvinyl alcohol.
[0072] In this embodiment, the base resin is o-cresol-formaldehyde epoxy resin.
[0073] In addition, this embodiment also provides a method for preparing a thermally conductive masterbatch, and the specific steps are as follows:
[0074] S1. Modification of surface adsorption: Modification of graphite emulsion by adding surface adsorbent;
[0075] S2. Masterbatch mixing process: the modified and refined graphite emulsion is mixed with the base resin at high temperature, the mixing temperature is 100°C, the mixing speed is 150rpm, and the mixing time is 30 minutes. The co-solvent and dispersant are removed to obtain a thermal conductive masterbatch.
[0076] The solid content of the thermal conductive masterbatch prepared in Example 1 was measured: by sampling ash test, it was determined that the content ratio of the effective graphite component was greater than 70%, and subsequent experiments were carried out.
[0077] Example 2
[0078] This embodiment provides a plastic packaging material containing a thermal conductive masterbatch, which includes the following raw materials in terms of mass percentage:
[0079]
[0080] Example 3
[0081] This embodiment provides a plastic packaging material containing a thermal conductive masterbatch, which includes the following raw materials in terms of mass percentage:
[0082]
[0083] Comparative Example 1
[0084] This embodiment provides a plastic packaging material, which includes the following raw materials in terms of mass percentage:
[0085]
[0086] Comparative Example 2
[0087] This embodiment provides a plastic packaging material, which includes the following raw materials in terms of mass percentage:
[0088]
[0089] Performance Testing
[0090] The plastic encapsulation materials prepared in Examples 2 to 3 and Comparative Examples 1 to 2 were subjected to thermal conductivity tests: thermal conductivity tests were performed according to ASTM E1530 (2019), a standard test method for evaluating the heat transfer resistance of materials using protected heat flow meter technology.
[0091] The thermal conductivity λ of the encapsulation material prepared in Example 2 is 0.754W / (m·K), the thermal conductivity λ of the encapsulation material prepared in Comparative Example 1 is 0.707W / (m·K), the thermal conductivity λ of the encapsulation material prepared in Example 3 is 0.883W / (m·K), and the thermal conductivity λ of the encapsulation material prepared in Comparative Example 2 is 0.811W / (m·K). The encapsulation material prepared in Example 2 is greater than the encapsulation material prepared in Comparative Example 1, and the encapsulation material prepared in Example 3 is greater than the encapsulation material prepared in Comparative Example 2. Therefore, the encapsulation material containing the thermal conductive masterbatch prepared in the present invention has a higher thermal conductivity.
[0092] like Figure 1-2 As shown, the carbon particles in the plastic packaging material containing the thermally conductive masterbatch prepared in Example 3 are connected to multiple small silica particles, and some carbon particles are directly connected to large silica particles, so that the heat conduction channel is bridged from the high thermal conductivity large particles, from the carbon particles, through the small particles until entering the next large particle, thereby improving the thermal conductivity.
[0093] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A thermally conductive masterbatch, characterized in that: The invention is composed of graphite emulsion, surface adsorbent and base resin, wherein the content of the graphite emulsion in the thermal conductive masterbatch is not less than 70wt%.
2. A thermally conductive masterbatch according to claim 1, characterized in that: In terms of mass percentage, the thermal conductive masterbatch comprises the following raw materials: Graphite emulsion 70% ~ 90%, Surface adsorbent 1% ~ 3%, Base resin 8% ~ 27%.
3. A thermally conductive masterbatch according to claim 1, characterized in that: The preparation method of the graphite emulsion is as follows: S1, mixing graphite powder, a solvent and a dispersant to obtain a graphite slurry; S2. Purify the graphite slurry obtained in step S1 to obtain graphite emulsion.
4. A thermally conductive masterbatch according to claim 3, characterized in that: In step S1, the graphite powder is ultrafine flaky microcrystalline graphite powder; The co-solvent is a ketone solvent or an alcohol solvent; The dispersant is selected from any one of sorbitol ester, monoglyceride, gelatin, and nano silica gel; In step S2, the purification treatment method is selected from static separation or low-speed centrifugal separation.
5. A thermally conductive masterbatch according to claim 1, characterized in that: The surface adsorbent includes a physical surface treatment component and / or a chemical surface treatment component; The base resin includes epoxy resin and / or phenolic curing agent.
6. A thermally conductive masterbatch according to claim 5, characterized in that: When the surface adsorbent includes both a physical surface treatment component and a chemical surface treatment component, the ratio of the physical surface treatment component to the chemical surface treatment component in the surface adsorbent is 1:1.5-2.5; The physical surface treatment component is an organic liquid, and the chemical surface treatment component is a cross-linking agent; The phenolic curing agent includes linear phenolic resin, p-tert-butyl phenolic resin, MAR phenolic resin, MAR phenolic resin (XYLOK), MAR phenolic resin (biphenyl type) and MFN multifunctional phenolic resin.
7. A method for preparing a thermally conductive masterbatch as claimed in any one of claims 1 to 6, characterized in that: The specific steps are as follows: S1. Surface adsorption enhancement treatment: Graphite emulsion is modified by adding surface adsorbent; S2. Masterbatch mixing process: The modified and refined graphite emulsion is mixed with the base resin at high temperature to remove the co-solvent and dispersant to obtain the thermal conductive masterbatch.
8. An application of the thermal conductive masterbatch as claimed in any one of claims 1 to 6, characterized in that: The thermal conductive masterbatch is used as a colorant in a plastic packaging material.
9. The use of a thermally conductive masterbatch according to claim 8, characterized in that: The plastic encapsulation material consists of silicon micropowder, epoxy resin, phenolic curing agent, silicone oil, demoulding wax and thermal conductive masterbatch.
10. The use of a thermal conductive masterbatch according to claim 9, characterized in that: When the epoxy resin is o-cresol epoxy resin and the phenolic curing agent is linear phenolic resin, the plastic encapsulation material includes the following raw materials in terms of mass percentage:
Citation Information
Patent Citations
Super heat resistance and high heat conduction epoxy molding compound used for semiconductor packaging
CN109467881A
Epoxy molding compound for high thermal conductivity and high magnetic induction packaging, preparation method and applications thereof
CN110776716A